1990
DOI: 10.1111/j.1439-0450.1990.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Granulocyte Functions: Evaluation and Modulation

Abstract: Summary Functions of porcine polymorphonuclear neutrophils are evaluated with in vitro test systems. Results are compared with those from human PMN and the relevance for in vivo conditions is discussed. Ethanol was inhibitory to all porcine PMN functions investigated here. Influex, a combination product, containing extracts of Echinacea, Aconitum, Apis and Lachesis stimulated adherence, chemotaxis, and phagocytosis, but inhibited chemiluminescence. These results suggest an effect of the product in the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results demonstrated that Echinacea had no impact on the parameters of the red and white blood picture of the pigs regardless of dosage and dosage form. This is in agreement with other authors (Wagner et al., 1986; Woestmann, 1986; Jurcic et al., 1989; Stahl et al., 1989). In the reported trials with different species, the hematologic parameters were not affected, but the rate of phagocytosis was enhanced.…”
Section: Discussionsupporting
confidence: 94%
“…The results demonstrated that Echinacea had no impact on the parameters of the red and white blood picture of the pigs regardless of dosage and dosage form. This is in agreement with other authors (Wagner et al., 1986; Woestmann, 1986; Jurcic et al., 1989; Stahl et al., 1989). In the reported trials with different species, the hematologic parameters were not affected, but the rate of phagocytosis was enhanced.…”
Section: Discussionsupporting
confidence: 94%
“…There are numerous recent reports indicating the immunostimulating or modulating effects of various preparations and extracts (Stimple et al 1984;Burger et al 1997;See et al 1997;Sun et al 1999;Currier and Miller 2001;Goel et al 2002). There are a few reports of the veterinary application of Echinacea therapy, for example, in horses (O'Neill et al 2002 ), swine (Stahl et al 1990) and cattle (Schuberth et al 2002) . Nothing has been reported on its use in poultry.…”
Section: Resultsmentioning
confidence: 98%
“…Further studies should check whether male animals are better suited. At present, ROS generation, which was quite often used to monitor immunomodulation by Echinacea preparations (Gaisbauer et al, 1990; Stahl et al, 1990; Roesler et al, 1991), cannot be recommended for the standard quality examination of phytomedicines in cattle.…”
Section: Discussionmentioning
confidence: 99%